Endovascular salvage of renal artery bypass in pediatric a patient with neurofibromatosis type 1 - Quynh-Anh L. Dang, BS, BBA; Alexander S. Fairman, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Neurofibromatosis type 1 (NF1) is a congenital vasculopathy that can affect the renal arteries, causing renovascular hypertension. We report a complex case of a pediatric NF1 patient who required endovascular salvage of a renal artery bypass. Treatment for pediatric renovascular NF1 requires close surveillance and the ability to pivot to rescue therapies.